2022
DOI: 10.1007/s11883-022-01023-9
|View full text |Cite
|
Sign up to set email alerts
|

More than Just a Monolayer: the Multifaceted Role of Endothelial Cells in the Pathophysiology of Atherosclerosis

Abstract: Purpose of the Review In this review, we summarize current insights into the versatile roles of endothelial cells in atherogenesis. Recent Findings The vascular endothelium represents the first barrier that prevents the entry of lipoproteins and leukocytes into the vessel wall, thereby controlling two key events in the pathogenesis of atherosclerosis. Disturbance of endothelial homeostasis increases vascular permeability, inflammation, and cellular trans-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 80 publications
0
37
0
1
Order By: Relevance
“…Raynaud’s phenomenon, or the onset of digital ulcers, may be considered a direct consequence of the imbalance between endothelium-derived relaxation and vasoconstrictive factors. Endothelial dysfunction is considered an early marker of atherosclerosis [ 37 ], so, therefore, we may assume that SSc could contribute per se to the development of accelerated atherosclerosis. Consistently, our findings ( Figure 1 and Figure 4 ) suggested that SSc could be involved in the pathogenetic chain of arterial stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…Raynaud’s phenomenon, or the onset of digital ulcers, may be considered a direct consequence of the imbalance between endothelium-derived relaxation and vasoconstrictive factors. Endothelial dysfunction is considered an early marker of atherosclerosis [ 37 ], so, therefore, we may assume that SSc could contribute per se to the development of accelerated atherosclerosis. Consistently, our findings ( Figure 1 and Figure 4 ) suggested that SSc could be involved in the pathogenetic chain of arterial stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…We do not maintain that these factors cause atherosclerosis but rather that they “prime the soil” in which lesions start to develop [ 20 ]. Endothelial cells are exposed to various degrees and types of shear stress, which have influence on their shape, intracellular signaling, and gene expression [ 21 ]. In the regular state, which is the quiescent state of the endothelium, nitric oxide (NO) is produced in order to bind to cysteine groups in NF-κB and the mitochondria, which inhibit cellular processes.…”
Section: Coronary Artery Disease and Atherosclerosismentioning
confidence: 99%
“…In the regular state, which is the quiescent state of the endothelium, nitric oxide (NO) is produced in order to bind to cysteine groups in NF-κB and the mitochondria, which inhibit cellular processes. Moreover, the endothelial layer is covered by a glycocalyx, which is layer of proteoglycans and extracellular matrix components, involved in transendothelial transport, e.g., of lipoproteins, which can be lost or reduced in inflammation due to plasminogen activator inhibitor [ 21 ]. In homeostasis, endothelial cells prevent platelet activation, blood clotting, and leukocyte adherence by secreting substances such as NO, prostacyclin, t-PA, and antithrombin III [ 21 ].…”
Section: Coronary Artery Disease and Atherosclerosismentioning
confidence: 99%
“…), the ECs can sense these danger-associated molecular patterns (DAMP) and pathogen-associated molecular patterns (PAMP), thus transduce the innate immunity related signaling pathways to counteract the deleterious effects of these endogenous and exogenous danger molecules. Once this counter measure is defective, the harmful effects will continue to surge and immune disorders perpetuate in multiple tissues and organs ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…ECs can facilitate the phagocytosis of LDL and its oxidatively modified form-oxLDL, leading to endothelial dysfunction ( 11 ). LDL can also undergo transcytosis across EC membrane by receptors such as SR-BI and ALK ( 5 , 12 ). During the advanced stage of atherosclerosis, cardiovascular risk factors can promote endothelial apoptosis, leading to endothelial denudation, plaque erosion and thrombus formation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%